2018
DOI: 10.1111/jep.12950
|View full text |Cite
|
Sign up to set email alerts
|

What is the guidelines challenge? TheCauseHealthperspective

Abstract: This paper is an introduction to the conference, The Guidelines Challenge, held in Oxford in October 2017. My aim is to explain our motivation for organising this conference, as part of the research project Causation, Complexity, and Evidence in Health Sciences (CauseHealth). Depending on the professional starting point, the guidelines challenge can be interpreted in a number of ways. Our idea with this conference was to discuss guidelines from 3 overarching perspectives: practice, policy, and philosophy. In p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…This picture is most likely an exaggeration of reality, but it is hard to deny that many scholars and practitioners tend to highlight EBM's shortcomings in ways that make it look like a cult. The number of charges against EBM include: (1) EBM provides, whether intentionally or not, a cookbook approach to medicine (see Feinstein and Horwitz 1997); 2EBM focuses almost exclusively on randomized controlled trials (see Cartwright 2018); (3) EBM provides too easy a framework for policy-makers and health care providers to constrain clinical practices and even refuse treatments that are not included in the approved guidelines (see Feinstein and Horwitz 1997), which are heavily biased towards randomized control trials (RCTs); and finally, among the peculiarly philosophical challenges, (4) EBM makes strong metaphysical assumptions and relies on a flawed positivist methodology (see Anjum 2018).…”
Section: Ebm a Debate Polarizedmentioning
confidence: 99%
See 1 more Smart Citation
“…This picture is most likely an exaggeration of reality, but it is hard to deny that many scholars and practitioners tend to highlight EBM's shortcomings in ways that make it look like a cult. The number of charges against EBM include: (1) EBM provides, whether intentionally or not, a cookbook approach to medicine (see Feinstein and Horwitz 1997); 2EBM focuses almost exclusively on randomized controlled trials (see Cartwright 2018); (3) EBM provides too easy a framework for policy-makers and health care providers to constrain clinical practices and even refuse treatments that are not included in the approved guidelines (see Feinstein and Horwitz 1997), which are heavily biased towards randomized control trials (RCTs); and finally, among the peculiarly philosophical challenges, (4) EBM makes strong metaphysical assumptions and relies on a flawed positivist methodology (see Anjum 2018).…”
Section: Ebm a Debate Polarizedmentioning
confidence: 99%
“…Accordingly, getting evidence for treatment and diagnostics will involve getting "knowledge about the individual patient and which causally relevant factor might affect the interaction with the treatment." (Anjum 2018(Anjum , p. 1129.…”
Section: Evidence In Evidence-based Medicinementioning
confidence: 99%
“…We are delighted to report that, in the year following these comments, we have received a vast amount of correspondence and submissions from some of the most insightful and influential commentators in health research and practice, taking this “great debate” forward in just the way we had hoped. This thematic edition of the Journal of Evaluation in Clinical Practice (the largest single edition of the JECP in its 24‐year history) includes over 50 papers, reviews, and reports of conferences that reflect the attention being given across the board—by practitioners, guideline developers, systematic reviewers, and philosophers—to the relationship between evidence, science, context, bias, truth, value, and methodology, with the quintessentially pragmatic goal to develop accounts of these concepts to assist decision‐making in practice. It includes specific sections consisting of papers delivered to major conferences on diagnostic categories (focussing on both their limitations and their overuse), clinical guidelines, and mechanisms in medicine .…”
Section: The Story So Farmentioning
confidence: 99%
“…The second paper, by Rani Lill Anjum, introduces the conference with a review of the challenges identified by the project core team to frame the discussion . Anjum provides a summary and reflection upon the interaction between philosophy, practice, and policy that the conference sought to bring to the fore and work within in respect to guidelines.…”
Section: The Guidelines Challengementioning
confidence: 99%
“…The themes for the “Guidelines Challenge” conference emerged from these events. A review of the introductory statements from CauseHealth Principal Investigator Rani Lill Anjum can be found within this issue of this journal . During these introductory statements, Anjum laid out the guidelines challenges that CauseHealth had marked as most important and urgent and how thinking of causality from the perspective of dispositionalism—a key component of the CauseHealth approach—can frame solutions to those challenges.…”
Section: Introductionmentioning
confidence: 99%